Porcelain: A Semantic Framework for Representing and Analyzing Memory Safety Techniques - Colle, Pedro Henrique Boniatti; Machado, Rodrigo (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2025)
At the start of the millennium, the Cyclone language was developed as a solution to the memory safety shortcomings of the C language. Since then, many programming languages have emerged with their own memory safety strategies. But how can we validate those strategies? This paper proposes Porcelain: a semantic framework for representing and analyzing memory safety techniques. Introducing its definitions, use cases, and limitations whilst giving an overview of the current and future work.